Knuckleball Ned - Dickey, R. A.
Ned the baseball is very nervous on his first day of school. Everyone else seems to know where they belong, but not Ned. He isn't a fastball or a slider, and the Foul Ball gang makes fun of him for the way he wobbles. When they do something particularly dastardly to another student, it's up to Ned to come to the rescue with his unique abilities. Not only does Ned realize he's a knuckleball, but he discovers that he can be a hero, too!